Anesthesia Management at Postpartum et causa Atonic Uteri Bleeding in P3A0H3 Post SCTP Outside Dr. Moewardi Hospital - RTh Supraptomo; Muhammad Ridho Aditya (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2021)
Postpartum hemorrhage remains the leading cause of maternal mortality and morbidity worldwide, happens more in developing countries with an estimated mortality rate of 140,000 per year or one maternal death every four minutesTo understand anesthesia management at postpartum et causa atonic uteri bleeding outside Dr. Moewardi hospitalIn this case reported 25 years old patient was admitted to the emergency room at Dr. Moewardi Hospital Surakarta, on the 28/11/2019 at 15.30 WIB, sent by Waras Hospital Wiris Boyolali. On examination found the patient in a state of weakness, apathy awareness and blood pressure 90/60, heart rate 130, respiration rate 22, conjunctival anemic and palpable contractions of soft uterine contractions. The patient's condition is in accordance with the manifestation of grade III blood loss. The anesthesiology diagnosis is a 25-year-old woman with Postpartum hemorrhage et causa Atonic Bleeding of Uterine on P3A0H3 post SCTP Outside Dr. Moewardi Hospital + Hypovolemic Shock pro Emergency Laparotomy until Total Abdominal Hysterectomy with Physical Status ASA IVE Plan with RSI general anesthesia Control.Intraoperative Management of anesthesia uses RSI's general anesthesia technique to control hemodynamics and uses anesthesia drugs that do not worsen the patient's condition. At the time of surgery, we did the transfusion because there was a significant amount of bleeding during the procedure and was categorized as Class IV bleeding.Anesthesia care of patients with postpartum hemorrhage extends from the antenatal period to the postpartum period. Optimal postpartum hemorrhage management occurs when nurses, obstetricians and anesthesiologists recognize early the potential for excessive bleeding and trigger a 'major obstetric hemorrhage protocol' that describes specific tasks for each team player and the algorithm that must be followed according to etiology, circumstances and time during labor.